Hypothalamic deafferentation and luteinizing hormone-releasing hormone on luteinizing hormone secretion in prepuberal beef heifers - Molina Villalobos, José Ramón ([editor no identificado], 1986)
Tesis (Doctor of Philosophy)--Iowa State University, 1986.